2020
DOI: 10.1111/ejss.13044
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐empirical model to predict the EM38 electromagnetic induction measurements of soils from basic ground properties

Abstract: Electromagnetic induction (EMI) measurements (σb*) are widely used for the survey of several soil attributes, among which basic properties such as salinity (σe), water content (θw), clay (wc), organic matter (wom) and bulk density (ρb) stand out. In usual practice, purely empirical models relating one of these properties to σb* are calibrated at selected sites. However, this calibration is site and time specific and has to be repeated time and again. In order to understand where the variability of the EMI empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In vineyards, these measurements have been correlated with vine stem water potential and berry composition [245]. This limitation comes from the fact that these measurements are usually related to soil properties through purely empirical correlations, which are site-specific and vary over time [244,246]. In a recent study, a semiempirical model represented the underlying physical process that affects electromagnetic induction signals and provided the basis for planning and comparing these measurements among different areas [246].…”
Section: Proximal Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In vineyards, these measurements have been correlated with vine stem water potential and berry composition [245]. This limitation comes from the fact that these measurements are usually related to soil properties through purely empirical correlations, which are site-specific and vary over time [244,246]. In a recent study, a semiempirical model represented the underlying physical process that affects electromagnetic induction signals and provided the basis for planning and comparing these measurements among different areas [246].…”
Section: Proximal Sensingmentioning
confidence: 99%
“…This limitation comes from the fact that these measurements are usually related to soil properties through purely empirical correlations, which are site-specific and vary over time [244,246]. In a recent study, a semiempirical model represented the underlying physical process that affects electromagnetic induction signals and provided the basis for planning and comparing these measurements among different areas [246]. However, the use of these sensors in vineyard management is nowadays limited to the delineation of site-specific management zones [10,247,248], which can be useful for precise and optimal irrigation scheduling.…”
Section: Proximal Sensingmentioning
confidence: 99%
“…One method for quickly and reliably assessing soil salinity across different locations is through electromagnetic induction (EMI) [7][8][9][10][11][12][13][14]. Electromagnetic instruments measure the apparent electrical conductivity of soil (EC a ; mS m −1 ), which is often strongly correlated with the electrical conductivity of saturated soil paste extract (EC e ) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic induction (EMI) measurements allow a fast non-contact measurement of the soil apparent electrical conductivity (ECa), which is directly related to the bulk soil electrical conductivity and thus to soil properties such as clay content, salinity and water content. EMI measurements have been used for soil mapping in precision agriculture in a wide range of studies [ 1 , 2 , 3 , 4 ]. For instance, Cameron et al [ 5 ], Visconti and Miguel de Paz [ 6 ] and Corwin and Rhoades [ 7 ] found that EMI allowed the fast mapping of the soil to obtain a clear delineation of field-scale salinity profiles.…”
Section: Introductionmentioning
confidence: 99%